Promotion and Upregulation of a Plasma Membrane Proton-ATPase Strategy: Principles and Applications - Ren, Zirong; Suolang, Bazhen; Fujiwara, Tadashi; Yang, Dan; Saijo, Yusuke; Kinoshita, Toshinori; Wang, Yin (Frontiers in Plant Science, 2021)
Plasma membrane proton-ATPase (PM H+-ATPase) is a primary H+ transporter that consumes ATP in vivo and is a limiting factor in the blue light-induced stomatal opening signaling-pathway. It was recently reported that manipulation of PM H+-ATPase in stomatal guard cells and other tissues greatly improved leaf photosynthesis and plant growth. In this report we review and discuss the function of PM H+-ATPase in the context of the promotion and upregulation H+-ATPase strategy, including associated principles pertaining to enhanced stomatal opening, environmental plasticity, and potential applications in crops and nanotechnology. We highlight the great potential of the promotion and upregulation H+-ATPase strategy, and explain why it may be applied in many crops in the future.